2013
DOI: 10.1038/srep01996
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processable graphene nanomeshes with controlled pore structures

Abstract: Graphene nanomeshes (GNMs) which can be cheaply produced on a large scale and processed through wet approaches are important materials for various applications, including catalysis, composites, sensors and energy related systems. Here, we report a method for large scale preparation of GNMs by refluxing reduced graphene oxide sheets in concentrated nitric acid solution (e.g., 8 moles per liter). The diameters of nanopores in GNM sheets can be readily modulated from several to hundreds nanometers by varying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 34 publications
(52 reference statements)
2
63
0
Order By: Relevance
“…For example, porous carbon nanosheets (CNS) prepared by oxidizing GO in HNO 3 media has been reported in the literature. [16,17] It is accepted that the edge-C and defect-C atoms on the GO surface can be detached and removed from the GO sheets with the existence of HNO 3 . Zhao et al fabricated porous carbon mesh by sonicating the GO suspension in diluted HNO 3 followed by the thermal reduction of the resultants.…”
Section: Chemical-etching Methodsmentioning
confidence: 99%
“…For example, porous carbon nanosheets (CNS) prepared by oxidizing GO in HNO 3 media has been reported in the literature. [16,17] It is accepted that the edge-C and defect-C atoms on the GO surface can be detached and removed from the GO sheets with the existence of HNO 3 . Zhao et al fabricated porous carbon mesh by sonicating the GO suspension in diluted HNO 3 followed by the thermal reduction of the resultants.…”
Section: Chemical-etching Methodsmentioning
confidence: 99%
“…Moreover, recent achievements have also demonstrated that the existence of in-plane nanopores not only improves the electrode utilization efficiency for charge storage, but also promotes the diffusion of electrolyte ion across the graphene 2D basal plane [34,35]. Among various methods, chemical activation of graphene with diverse activation agents, including KOH [36][37][38], metal oxides [32,39], KMnO 4 [40] and concentrated HNO 3 [41] have been successfully utilized to oxidize carbon atoms to produce in-plane nanopores. However, construction of these 2D porous graphene sheets into a macroscopically 3D architecture for practical applications still remains a great challenge [32,42].…”
Section: Introductionmentioning
confidence: 99%
“…These pores are formed during the solar exfoliation process due to the rapid reaction. The pores play an important role in the proper wetting of the surfaces while in contact with the electrolytes and can avail all the stacked surfaces for the adsorption of the materials [9]. Fig.…”
Section: Resultsmentioning
confidence: 99%